Kepraktisan E-Modul Flip Materi Lingkaran Berbasis Problem Based Learning - Limalo, Sri Agustin; Abbas, Nurhayati; Panigoro, Hasan S. (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This study aims to test the practicality of the problem-based mathematics e-module based on circle material. The type of research used is comparative descriptive research. The subjects of this study were teachers and students of class IX at SMP Negeri 2 Tilamuta. The results showed that the assessment of using Problem Based Learning -based mathematics e-modules received positive responses from teachers with an average percentage of 87.23% and positive responses from students with an average percentage of 78.45%. The average percentage of teacher and student responses is in the very good category, the module meets the practical criteria. Based on the study result, it can be concluded that the Problem Base Learning -based mathematics e-module, Circle material, fulfils practicality so it is suitable for use in learning.